Complete blood count reflecting the disease status of giant cell arteritis: A retrospective study of Chinese patients. Issue 39 (25th September 2020) - Yin, Yue; Zhang, Yun; Wang, Dongmei; Han, Xinxin; Chu, Xiaotian; Shen, Min; Zeng, Xuejun
Abstract : Abstract: Giant cell arteritis (GCA) is the most common vasculitis in elderly, with ischemic and constitutional symptoms caused by vascular involvement and systemic inflammation. Early initiation of therapy results in prompt remission, while patients may still experience flares or severe complications during glucocorticoid tapering. This study was to identify the characteristics of Chinese GCA patients with different prognosis. Ninety-one patients diagnosed with GCA in Peking Union Medical College Hospital in the last 20 years were followed up. Those who were lost to follow up or were followed up for less than 1 year were excluded. According to the prognosis, patients were divided into the group of favourable prognosis (patients who sustained disease remission for over 1 year) and unfavorable prognosis (patients who had relapses or severe complications). Clinical data at disease onset and after treatment were collected and analysed between the 2 groups. Thirty-seven patients with favourable prognosis and 40 patients with unfavourable prognosis were admitted into the study. Fever as an onset symptom was less common in favourable group ( P =.016). As for presentations of GCA, fever, tenderness and abnormal pulsation of temporal artery and jaw claudication were less frequently observed in patients with favourable prognosis ( P =.029, .049, .043, respectively). At onset, medium-size arteries were affected more in unfavorable prognosis group ( P = .048), and involvement of branches below the aortic arch were more common in favorable prognosis group ( P = .034). Erythrocyte sedimentation rate in group of favourable prognosis were significantly lower after treatment ( P = .041). Compared with healthy subjects, GCA patients had increased monocytes and decreased lymphocytes at disease onset ( P < .01). Monocyte counts were higher in patients with favourable prognosis at disease onset ( P = .043), while no significant differences were seen between the 2 groups after treatment. Lymphocyte counts were lower in patients with unfavourable prognosis ( P = .014) after treatment. Complete blood count may reflect the disease status of GCA. Little change in monocyte during treatment and lower lymphocytes after treatment may serve as potential predictors of unfavourable clinical prognosis.